Research on a highly sensitive surface plasmon resonance sensor based on side-polished holey fiber with circle lattice - Liao, Jian-Fei (Oficyna Wydawnicza Politechniki Wrocławskiej, 2024)
Using the strong local electromagnetic field enhancement of surface plasmon polaritons (SPP), a highly sensitive surface plasmon resonance (SPR) sensor based on side-polished circle lattice holey fiber (HF) is proposed. The coupling resonance properties of the sensor are numerically studied, and the investigation findings indicate that our proposed sensor can realize single-resonance detection within a wide wavelength range of 1.189–1.921 μm for the refractive index (RI) of the analyte changes from 1.28 to 1.39. The highest wavelength sensitivity, amplitude sensitivity, and RI resolution are up to 21,400 nm/RIU, 363.4 RIU–1, and 4.67 × 10–6 RIU, respectively. Therefore, our proposed sensor will have broad application prospects in RI sensing, including water pollution monitoring, medical treatment, and food safety detection.
Optica Applicata, Vol. 54, 2024, nr 3, s. 317-326
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; sensor; surface plasmon resonance; holey fiber; fiber optics